Post-Traumatic Stress Disorder in Military Personnel: A Comparative Analysis of Rehabilitation Strategies in the Ukraine - Inna Osadchenko; Nina Tverezovska; Iryna Demchenko; Oleksandra Drachuk; Nataliia Hrynova (The International Journal of Psychiatry in Medicine, 2026)
Objective The psychological rehabilitation of military personnel with post-traumatic stress disorder (PTSD) gained critical importance during the armed conflict in Ukraine (2022-2026). This study compared the effectiveness of alternative approaches to PTSD rehabilitation for Ukrainian soldiers and provides recommendations for optimizing psychological assistance. Methods A longitudinal study was conducted with 512 Ukrainian service members with clinically significant PTSD who received support in state rehabilitation centres and private psychological programs between 2022 and 2025. Participants were non-randomly divided into 3 groups: an experimental group (n = 204) receiving a comprehensive program, a group (n = 188) following a standardized international protocol, and a control group (n = 120), based on practical constraints related to the availability of specialized rehabilitation programs. PTSD symptoms were assessed before and after the interventions using the PCL-5. Results Those participating in the comprehensive program achieved the most significant reduction in PTSD symptoms, from 51.2 to 28.5 points on the PCL-5 scale (44.3% reduction), compared to a 36.3% reduction in the international protocol group and 5.4% in the control group. Additionally, the comprehensive program showed a 50.2% reduction in depressive symptoms, a 49.2% decrease in anxiety, and an 89.8% improvement in quality of life. The greatest impact was on avoidance symptoms, which decreased by 61.5%, linked to art therapy integrated into cognitive behavioural therapy. Conclusion These results emphasize the need for a national clinical protocol for comprehensive PTSD rehabilitation and the training of specialists in trauma-informed care to support military personnel in the Ukraine.